Public Administration reforms and results - Kristinsson, Gunnar Helgi; Matthíasson, Pétur Berg (Stjórnsýslustofnun, 2014)
Research on administrative reforms during the past thirty years indicates that reform efforts of countries differ. The Anglo Saxon states were at the forefront of the New Public Management movement while countries on mainland Europe were more hesitant and moved further towards the Neo-Weberian state. Academics have tried to explain different reform efforts within countries by looking at political, historical and cultural issues, values and economic factors to name just a few. Three hypotheses are put forward to explain reform efforts in different states. This research involves analysing the implementation of two different reform trends, New Public Management and the Neo-Weberian tradition. The analysis indicates that countries vary in their commitment to reform rather than in the emphasis on either New Public Management or the Neo-Weberian State. Decentralization, clear objectives and consultation with communities and experts are closely related to national reform efforts. However, Iceland does distinguish itself from Europe and the Nordic countries. The analysis reveals that although decentralization is high in the Icelandic system, autonomy of agencies does not have a strong relation to a varied use of administrative instruments. The second part of the article focuses on the results and achievements of reform programmes. The achievement of reform programmes are examined in relation to theories of bounded rationality, street level bureaucracy (bottom up) and consensus decision making. Three hypotheses are presented and tested to explain what causes reforms programmes to be successful in some countries and not in others. The analysis reveals that countries are more likely to succeed if bounded rationality is applied with careful preparation and when stakeholders are consulted. Rannsóknir undanfarna þrjá áratugi á innleiðingu umbóta benda til þess að umbótaviðleitni ríkja sé mismunandi. Engilssaxnesk ríki voru áberandi við innleiðingu hugmyndafræði nýskipunar í opinberum rekstri á meðan ríki á meginlandi Evrópu ...